One-Pot, Metal- and Azide-Free Synthesis of 1,2,3-Triazoles from α-Ketoacetals and Amines - Zehnder, Luke R.; Hawkins, Joel M.; Sutton, Scott C. (Synlett, 2020)
An efficient one-pot two-step synthesis of 1,4-disubstituted 1,2,3-triazoles from α-ketoacetals and amines is presented. The method does not use metals, azides, or oxidants, and is compatible with a variety of functional groups, including heterocycles, esters, nitriles, and carbamates.
Keywords: triazoles; ketoacetals; metal-free; azide-free; one-pot synthesis; Sakai reaction